Involving young people in changing their school environment to make it safer: Findings from a process evaluation in English secondary schools. Issue 3 (1st June 2015) - Fletcher, Adam; Fitzgerald-Yau, Natasha; Wiggins, Meg; Viner, Russell M.; Bonell, Chris
Abstract : Purpose: – The purpose of this paper is to explore the process of involving students and staff on school action groups, and staff and student experiences of reviewing local data and initiating school-level changes, to address bullying and other aggression. Design/methodology/approach: – The authors draw on qualitative, process data collected at four purposively sampled pilot intervention schools in England via semi-structured interviews with school managers, action group members and facilitators ( n =33), focus groups with students ( n =16) and staff ( n =4), and observations. Findings: – School staff used multiple methods to recruit a diverse range of students onto school action groups. Locally tailored data reports were an important catalyst for action groups to identify priorities and plan whole school change – both through the process of "validation" (whereby existing concerns were confirmed) and "discovery" (whereby new problems were identified). An unexpected benefit of providing schools with these data was that it triggered analyses of other data sources, including routine monitoring data. External facilitators were important in promoting student voice and ensuring the intervention retained integrity as a whole-school restorative approach. Practical implications: – It was feasible to involve young people using action groups, and there was evidence of school-level actions led by students, including in disadvantaged school contexts. Future Health Promoting Schools interventions could incorporate this approach to support locally appropriate, school-level change. Originality/value: – The micro-level processes that were observed, whereby action groups interrogated feedback reports and collected additional data, suggest the responsiveness of such youth-involvement interventions to local needs. Contrary to many public health interventions, implementation appeared to be facilitated rather than hindered by features of the secondary-school "market" whereby parents have some choice between schools.